How does the exosite of rhomboid protease affect substrate processing and inhibition?. (24th October 2017) - Shokhen, Michael; Albeck, Amnon
Abstract: Rhomboid proteases constitute a family of intramembrane serine proteases ubiquitous in all forms of life. They differ in many aspects from their soluble counterparts. We applied molecular dynamics (MD) computational approach to address several challenging issues regarding their catalytic mechanism: How does the exosite of GlpG rhomboid protease control the kinetics efficiency of substrate hydrolysis? What is the mechanism of inhibition by the non‐competitive peptidyl aldehyde inhibitors bound to the GlpG rhomboid active site (AS)? What is the underlying mechanism that explains the hypothesis that GlpG rhomboid protease is not adopted for the hydrolysis of short peptides that do not contain a transmembrane domain (TMD)? Two fundamental features of rhomboid catalysis, the enzyme recognition and discrimination of substrates by TMD interactions in the exosite, and the concerted mechanism of non‐covalent pre‐catalytic complex to covalent tetrahedral complex (TC) conversion, provide answers to these mechanistic questions.